TheMovementPlus SizeandtheBody (ModaPalavra e-periódico, 2019)
Thebeautifulbodysenseeffectsaresociallyandhistoricallyprogressive,markedbycultural,social,class,politicalorreligiousstereotypes.Themediaandfashionalsohaveastronginfluenceonthebeautystandardsimposed.Themediaappearsasaprivilegedplaceofconstitution,formulationandcirculationofthesensesofwhatcanbeabeautifulbodyornot,legitimatinginstitutionsthatdeterminewhatcanandcan’tbesaid/shownindifferentspaces.Fashion,inturn,isamarketspace.Thus,theplussizemovementemergesasaneedforacceptanceandinteractionoffatbodiesinfashion.However,theconditionofthefatbodydoesnotchange,appointmentsarechangedtoproduceaneffectofwhichthisbodyispossible,butit remains impossible within the standardizationaspects of institutions
Keywords: fashion; nedia; body